2009
DOI: 10.1088/0953-4075/42/14/141003
|View full text |Cite
|
Sign up to set email alerts
|

Bright and dark periods in the entanglement dynamics of interacting qubits in contact with the environment

Abstract: Interaction among the qubits are basis to many quantum logic operations. We report how such inter-qubit interactions can lead to new features, in the form of bright and dark periods in the entanglement dynamics of two qubits subject to environmental perturbations. These features are seen to be precursors to the well known phenomenon of sudden death of entanglement [Yu & Eberly, Phys. Rev. Lett. 93, 140404 (2004)] for noninteracting qubits. Further we find that the generation of bright and dark periods are gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 43 publications
4
36
2
1
Order By: Relevance
“…Generally speaking, the amplitude of concurrence decays rapidly at the initial process owing to the interaction between the qubits and their environment, and then rebounds before eventually trending to a constant value because the tunable terms in (1) have larger contributions than decay terms from the environment at a longer evolving time. It is worth mentioning here that, for the case of ω = 0, we can get the ESD as shown by Das and Agarwal [33][34][35]. For the case of ω = 0 with ζ = 8 1 , we see from Fig.…”
Section: Concurrence For the Antiferromagnetically Coupled Qubitssupporting
confidence: 61%
See 1 more Smart Citation
“…Generally speaking, the amplitude of concurrence decays rapidly at the initial process owing to the interaction between the qubits and their environment, and then rebounds before eventually trending to a constant value because the tunable terms in (1) have larger contributions than decay terms from the environment at a longer evolving time. It is worth mentioning here that, for the case of ω = 0, we can get the ESD as shown by Das and Agarwal [33][34][35]. For the case of ω = 0 with ζ = 8 1 , we see from Fig.…”
Section: Concurrence For the Antiferromagnetically Coupled Qubitssupporting
confidence: 61%
“…However, the feature of bright and dark periods in the evolving curve of concurrence is not found in Fig. 1 due to the existence of ω, which is different from the results given by Das and Agarwal [33][34][35]. Note that, for the parameters ζ = 9 1 and ζ = 10 1 , Fig.…”
Section: Concurrence For the Antiferromagnetically Coupled Qubitscontrasting
confidence: 55%
“…For specific initial states, the entanglement generated by the dissipative evolution may exhibit a delayed feature, which is called the delayed sudden birth of entanglement [18][19][20][21]. In particular, it has been found that for a two-atom system with a nonvanishing separation immersed in a thermal bath, entanglement sudden birth only happens for atoms with an appropriate separation in a thermal bath at sufficiently small temperatures, while entanglement sudden death is a general feature [21].…”
Section: Introductionmentioning
confidence: 99%
“…Differently from Ref. [23] in the Markov approximation, however, our model includes interaction between the coupled qubit system and the environment in the non-Markov process. By choosing the symmetric coupling between the qubit and the environment, therefore, the effect of environment would disappear similar to the non-decoherence subspace, which may be an effect way to avoid the entanglement decay.…”
Section: Entanglement Dynamicsmentioning
confidence: 99%